(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the anti-leishmania activity of extracts and fractions from stem and leaf of Montrichardia linifera against Leishmania amazonensis. The stem (EES) and leaf (EEL) extracts were obtained by maceration of powders with 96º GL alcohol. The extracts were subjected to exhaustive extraction using a reflux system and solvents of increasing polarity, obtaining 4 fractions for each extract: hexane, dichloromethane, ethyl acetate and methanol. The extracts and fractions were submitted to a phytochemical prospecting study. The antipromastigote activity and cytotoxicity in macrophages (J774) were performed using the cell viability test (MTT). In the extract and fractions of the stem, alkaloids, steroids, terpenes, flavonic heterosides, tannins, polyphenols and saponins were detected. In the extract and fractions of the leaves, coumarins, steroids, terpenes, flavonic heterosides, tannins, polyphenols and saponins were detected. In the anti-leishmania evaluation, the hexane fraction of the leaf (HFL) showed promising activity (IC50=38.56 µg/mL), and the hexane fraction of the stem (HFS) showed moderate activity (CI50=179.3 µg/mL), the extracts and the other fractions were inactive (IC50>200 µg/mL). In the cytotoxicity test, EES and HFS were cytotoxic (CC50 54.82 µg/mL and 26.95 µg/mL, respectively). EEF and HFL showed moderate cytotoxicity (CC50 of 162.7 µg/mL and 347.1 µg/mL). As for the selectivity index, the HFL showed high selectivity (SI=90). In summary, fractionation contributed to increase anti-leishmania activity and the selectivity of HFS, such activity may be related to steroids or terpenes.